Between film, video, and the digital hybrid moving images in the post-media age - Kim, Jihoon (New York Bloomsbury Academic, 2018)
"A wide-ranging theoretical and aesthetic exploration of hybrid moving images based on the intersection of film, video, and digital technology"-- Provided by publisher.
Chapter 1: Videographic Moving Pictures: Remediating the "Film Stilled" and the "Still Film" -- Chapter 2: Digital Glitch Video and Mixed-media Abstraction: Materialism and Hybrid Abstraction in the Digital Age -- Chapter 3: Transitional Found Footage Practices: Video In and Out of the Cinematic Fragments -- Chapter 4: Intermedial Essay Films: "Memories-in-Between" Chapter 5: Cinematic Video Installations: Hybridized Apparatuses inside the Black Box Afterword.
Includes bibliographical references and index.
Keywords: Motion pictures -- Philosophy; Digital media -- Philosophy; Image processing -- Digital techniques